Citystats and the History of Community and Segregation in Post-Second World War Urban Canada - Stanger-Ross, Jordan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThis article introduces an open access website—citystats.uvic.ca —designed to facilitate historical scholarship on ethnicity in post-Second World War Canada. Citystats offers access to two sociological measures of urban residential patterns, D and P*, applying the measures to the ethnic origins variables in the Canadian census for all urban areas since 1961. D, the index of dissimilarity, is the most common gauge of urban residential patterns, describing the extent to which ethnic groups are evenly (or unevenly) distributed across the city. P*, a measurement of the exposure of groups to one another, provides historians with a summary of the everyday surroundings of urban residents. The article explains the measures and highlights some puzzling patterns in the history of urban Canada, especially the segregation of Jewish Canadians and the relative integration of Aboriginal people. Just as scholars might be expected to know (at least approximately) the number of people comprising the group that they intend to study, they should also, I argue, be aware of their distribution across urban space and their exposure to other urbanites.